Trends in the representation of women in the American Society of Pediatric Nephrology program at the Pediatric Academic Society annual meetings 2012–2021 - Barani-Najafabadi, Bahar; Selewski, David T.; Soranno, Danielle E.; Weidemann, Darcy K. (Frontiers in Pediatrics, 2023)
Women are under-represented in virtually all fields of academic medicine. Even in pediatrics, a field that historically attracts a workforce with a majority of women physicians, substantial gender disparities persist in leadership positions. However, previous studies of gender representation in various academic settings are limited to small studies or aggregate pediatric subspecialties, thereby omitting important granularity within each subspecialty. No prior studies have investigated potential gender disparities in pediatric nephrology. The aim of this study is to determine the representation of women physicians in leadership and speaking roles in the annual American Society of Pediatric Nephrology (ASPN) meeting. Data were analyzed from the 2012-2022 ASPN annual scientific meetings at the Pediatric Academic Society (PAS). Data were abstracted regarding gender and roles: speaker, chair/moderator, and lifetime achievement awardee. We performed a time series analysis using linear regression, with the year as the independent variable and the proportion of women as the dependent variable. Overall, there were statistically significant increases in the proportion of women speakers per year and percentage of women chairs or moderators. There were no specific trends noted for lifetime achievement awards and no statistically significant changes in the number of lifetime achievement awards. We found proportionate representations of gender representation with regards to speakers and chairs or moderators, although our data was limited by comparison to the American Board of Pediatrics (ABP) workforce cumulative “ever certified” data. The ABP data include a disproportionate representation of faculty who are men from earlier certification periods who may no longer be actively practicing pediatric nephrology.